UPAYAÂ MENUMBUHKANÂ KREATIVITASÂ ANAKÂ DENGANÂ Â PERMAINANÂ MATEMATIKA - achmad hidayatullah (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
TheÂ  developmentÂ  ofÂ  moreÂ  advancedÂ  affectsÂ  parents.Â  MostÂ  parentsÂ  wishedÂ  forÂ  her cleverÂ  countingÂ  etc.Â  BecauseÂ  demandÂ  isÂ  soÂ  greatÂ  wouldÂ  beÂ  aÂ  problemÂ  ifÂ  theÂ  expectations imposedÂ  onÂ  earlyÂ  childhoodÂ  inÂ  aÂ  spanÂ  ofÂ  2â€7Â  years.Â  EducationalÂ  institutionsÂ  alsoÂ  as playgroupÂ  asÂ Â theÂ  ageÂ  ofÂ  arithmeticÂ  thatÂ  isÂ  notÂ  appropriateÂ  forÂ  children.Â  BecauseÂ  on the oneÂ  hand,Â  earlyÂ  childhood,Â  stillÂ  inÂ  play.Â  ButÂ  bothÂ  ofÂ  themÂ  canâ€™tÂ  beÂ  disputedÂ  andÂ  faced resistance.Â  AÂ  BothÂ  ofÂ  themÂ Â canÂ  beÂ  bridgedÂ  byÂ  theirÂ  mathematicalÂ  educationalÂ  gamesÂ  in orderÂ  toÂ  enhanceÂ  theÂ  creativityÂ  ofÂ  children.Â  SoÂ  inÂ  earlyÂ  childhoodÂ  shouldÂ  beÂ  targetedÂ  not cognitiveÂ  intelligenceÂ  butÂ  theÂ  creativityÂ  ofÂ  children.Â  Therefore,Â  thisÂ  studyÂ  willÂ  focusÂ  howÂ  to fosterÂ theÂ creativityÂ ofÂ childrenÂ withÂ mathÂ games.Â TheÂ approachÂ inÂ thisÂ studyÂ usingÂ literatif study.Â IsÂ toÂ findÂ variousÂ referencesÂ toÂ giveÂ anÂ answerÂ toÂ theseÂ problems. Â Keywords:Â  Education,Â CreativityÂ andÂ MathematicsÂ games